Analysis on Farmers' Decision-Making Processes Regarding Sustainable Agricultural Practices: A Case Study in Kademangan, Pagelaran, Malang, Indonesia - Bias Tri Banadi; Abdul Wahib Muhaimin; Agustina Shinta (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2024)
Pagelaran, located in Malang, is among the seven key rice-producing regions, encompassing an agricultural expanse of 2,592 hectares. Despite this, a notable scarcity persists in the adoption of sustainable agricultural practices among local farmers, such as the utilization of organic fertilizers and integrated pest and disease management within their agricultural enterprises. The investigation centered on Kademangan, Pagelaran, Malang, Indonesia. Employing a purposive sampling approach, the study engaged 66 respondents. Data synthesis encompassed primary and secondary sources. Methodologies encompassed descriptive analysis, Structural Equation Model (SEM), and Analytical Hierarchy Process (AHP). Outcomes underscored the significant impact of innovation characteristics on farmers' attitudes, intentions, and decisions. Additionally, attitudes and moral norms emerged as influential determinants of farmers' intentions and decisions. Perceived behavioral control and intentions were pivotal in shaping farmers' decisions. Notably, strategies aimed at enhancing farmer capacity pertaining to sustainable agriculture emerged as paramount in augmenting its implementation, as per the study's findings.